2020
DOI: 10.1182/blood-2020-141435
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Jagged1 Is Required for the Transition of Hematopoietic Stem Cells from the Fetal Liver to the Adult Bone Marrow Niche

Abstract: Notch signaling is known to play important roles in hematopoietic development and differentiation. Notch1 is required for emergence of the definitive hematopoietic stem cells (HSCs) from the hemogenic endothelium, and we have previously shown that Notch signaling is essential for survival and function of HSCs in the fetal liver. Activation of canonical Notch signaling requires direct cellular contact; thus, the identity of the ligand and the ligand-presenting cell during hematopoietic development would provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…31 ). Both LGALS1 67 and JAG1 68 have been shown to be involved in hematopoiesis, however, the specific roles in this process is not as well-characterized. In topic 5, we observed the persistence of an IRF8 -specific network from the HSCs/MPPs to LMPs populations, which was lost in MEMPs/GPs lineage and is consistent with our k-means analysis and our results from Buenrostro et al (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…31 ). Both LGALS1 67 and JAG1 68 have been shown to be involved in hematopoiesis, however, the specific roles in this process is not as well-characterized. In topic 5, we observed the persistence of an IRF8 -specific network from the HSCs/MPPs to LMPs populations, which was lost in MEMPs/GPs lineage and is consistent with our k-means analysis and our results from Buenrostro et al (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using Rag-1 -/- mouse stem cells, Stier et al ( 40 ) documented Notch1-induced reduction of in vivo differentiation and an increased stem cell population due to enhanced stem cell self-renewal. The research of Shao et al ( 41 ) revealed that endothelial Jagged1-Notch1 deficiency severely affects the development of fetal blood vessels and impedes the proliferation and differentiation of HSCs in vitro and in vivo . Additionally, it was specified that Notch1-Hes1 may act on hematopoietic precursor cells, which are produced following the fate of HSCs.…”
Section: Notch1 and Hscsmentioning
confidence: 99%